Influence of individual and institutional factors on opportunity recognition and new venture creation among SME women entrepreneurs in India - Choudhary, Jyoti (2020)
The interest in women entrepreneurship is on the rise. Despite, the increase in the number of women entrepreneurs, a persistent gender gap in entrepreneurship is observed worldwide, and has been a cause of concern among researchers and practitioners. In India, the gender gap in entrepreneurship is highest in the world and women are pre- dominantly operating in the micro sector. It has been acknowledged that India cannot achieve its sustainable development goals without increasing the women participation in new venture creation across Small & Medium Enterprises (SME).